Tex e os tipos raciais: 1953-2000 - Antunes, Aline Ferreira (2019)
This work is a presentation of the Masters research developed in the area of Cultural History by the Federal University of Uberlândia (UFU) between 2016 and 2018. It addresses the central theme of the research that deals with an analysis of the racial types present in the TEX magazines of the groups: Chinese, Mexican, Native Americans and Black, as well as their relationship with the main character of the fumetti (Comics in Italian), Tex Willer. In addition, I bring the methodology, the objectives, justification of the work, problems as well as the partial considerations of the research. Based on communication authors (Vergueiro, Barbieri) and Cultural History (Burke, Chartier) I have linked it to Western themes (Limerick, Hughes), racial theories (Banton, Black and Solomos) to better analyse the source. The historical sources were chosen according to the theme and are presented throughout chapters 2 and 3, while chapter 1 is reserved an approach about the main character and its characteristics, as he is a comic hero very consumed in Italy (since 1948) and in Brazil (since 1971). Perceiving how Giovanni Luigi Bonelli (creator of the scripts) and Aurelio Galleppini (creator of the drawings) sought inspiration and dialogue with the Western Spaghetti cinema to enact his character who is a ranger, cowboy, avenger, chieftain of the Navajo and Indian agent, a "good guy of the West" that is part of the Italian imagination and that for many years was present in the newsstands and newspapers of Brazil.